Active noise control using adaptive filter approaches - 446191 Mohd. Hazrin Mohd. Dalhal (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2002